Implementasi Akad Wadiah pada Tabungan Haji IB Makbul di PT Bank Sumut Kantor Cabang Pembantu Syariah Binjai - Ningsih, Devi Aprilia; Jannah, Nurul (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study was to find out how the implementation of wadiah contracts in iB Makbul Hajj savings at PT. Bank Sumut Sharia Binjai Sub-Branch Office and to find out the conformity of the iB Makbul Hajj savings procedure with the wadiah contract at PT. Bank of North Sumatra Binjai Sharia Sub-Branch Office. The research method used in this study is a qualitative descriptive method. Data collection was carried out by interviewing one of the employees of PT. Bank of North Sumatra Binjai Sharia Sub-Branch Office, and direct or indirect observations of objects related to the researched. The results of this study are the implementation of the wadiah contract in the iB Makbul Hajj savings run by PT. Bank Sumut Sharia Binjai Sub-Branch Office is a wadiah yad dhamanah contract and also a Hajj iB Makbul savings product at PT. Bank Sumut Sharia Binjai Sub-Branch Office in accordance with applicable regulations